Correlates of Health Behavior in Urban Poor Communities - Mensah, K.O. (University of Ghana, 2015)
Despite an increase in the number of people living in poor urban communities in Ghana, little is known about their health behavior. This study examined the correlates of health behavior in three urban poor communities in Accra, Ghana. The third round of EDULINK survey carried out by the Regional Institute for Population Studies from August-September, 2013 Agbogbloshie, James Town and Ussher Town was used. A total of 775 individuals aged 15-59 years were selected for the survey and formed the sample size for this study. Four variables were used to generate an index for health behavior. These are: smoking, alcohol consumption, salt intake and engagement in physical activity. The scores ranged from 1 to 4 and the higher the score, the better the health behavior. The data were analyzed using descriptive statistics, Chi-Square tests and cross tabulations, and ordinal logistic regression respectively. The results showed that the highest proportion of respondents (41.3%) engaged in bad health behavior. At the bivariate level, the findings showed that age, sex, religion, marital status, occupation and risk perceptions of heart disease were significantly associated with health behavior. Further, at the multivariate level of analysis, the results showed that age, religion, locality and risk perception of heart diseases were correlates of health behavior. Specifically, the log-odds of engaging in healthy behavior was higher among the younger age groups, Muslims, those living in Agbogbloshie and those who perceived themselves to be of no risk of heart diseases. This study showed that socio-demographic characteristics of the respondents in these communities matter with regard to enhancing health behavior. Based on the findings, the study recommends that policy targets people in the older age and others who engaged in unhealthy behaviors by giving them effective education on adopting a healthy behavior. Also, the study recommends that future studies adopt a longitudinal approach in the study of the correlates of health behavior in these communities so as to be able to establish causality.
Thesis(M.A)-University of Ghana, 2015
Keywords: Health Behavior; Urban Poor Communities